«Brace yourselves! Video Surveillance is coming»: the situation of video surveillance in the Peruvian Legal System - Murillo Chávez, Javier André (2019)
This article seeks to analyze the legal bases of video surveillance, the state of the current unsystematic regulation in the Peruvian legal system and the first juridical-factual consequences that are emerging from its progressive application. In this way, the article begins with the study of the protection of the image of the person, with special attention to the phenomenon of video surveillance, from the point of view of Civil, Constitutional, Administrative and —even— Criminal law. Later, it studies the way in which the Legislator and —in other cases— the Executive have established the specific and particular rules on video surveillance in Peru at the national level. Finally, it continues with the description and analysis of some of the factual assumptions that have been challenging Peruvian authorities; among which we have the use of video surveillance as a method of monitoring by entities for security purposes, as a tool for the use of employers to detect labor infractions, as an obligation of the service providers to guarantee the security of the consumers, and as evidence of the correct conduct at the start and ending of a family visit’s regime when sons or daughters are taken out of regular home, this last is an example of the use of recorded video material of the private form or material of video surveillance as evidence in judicial and/or administrativeproceedings.